A Retrospective Study to Find out Risk Factors and Management of Ectopic Pregnancy (Delta Medical College Journal, 2025)
Background: Ectopic pregnancy occurs in 2% of all pregnancies and is a potentially life-threatening emergency. The exact aetiology of ectopic pregnancy is unknown although a number of risk factors have been identified. Objective: The present study was conducted to explore the clinical presentation, probable risk factors, associated maternal morbidity and mortality with respect to ectopic pregnancy and its management. Materials and method: The present study involves a retrospective analysis of ectopic pregnancies admitted in BIRDEM General Hospital for two years from January 2020 to December 2021. Relevant data of all the 47 patients diagnosed and treated as ectopic pregnancy during the study period were collected from hospital records and included in this study. Results: The majority of the cases (62%) were between 20-30 years of age, and majority of them were from the lower middle class (64%). Most of the patients were multigravida (77%). Probable risk factors could be identified in 76.59% of cases among which history of previous abortions were morecommon (36.17%). Abdominal pain was the most common symptom seen in 96% cases. On ultrasound, the most common finding was adnexal mass (38.29%). In the majority of patients (53.19%), the ampullary region of the fallopian tube was the site of ectopic pregnancy. Among the 47 patients, 42(89.36%) underwent surgery, 3 patients (6.38%) underwent medical management and 2 patients (4.25%) received expectant management. Conclusion: The most common site of ectopic pregnancy was ampulla of fallopian tube. Ruptured ectopic is a common complication. Early diagnosis and early intervention are necessary for maternal survival.Delta Med Col J. Jan 2022;10(1): 4-9